ETHICAL ASPECTS OF THE BEHAVIOR OF PUBLIC SERVANTS - Krykun, Olga (Social Economics, 2022)
Abstract. The article analyzes the problems of conflict of interest of civil servants. The relevance of the study is that at the present stage the ethics of civil service is a type of managerial ethics, based on which the professional morality of civil servants is studied, and value orientations, ethical norms, moral aspects of behavior, relationships between people in public administration are substantiated. The microethics of a civil servant reveals specific requirements for the morality of civil servants, which are related to the peculiarity of the profession, its institutional, organizational and personal ethical components.Professional ethics should characterize the high culture in the work of all parts of the state administration. The ethics of a civil servant substantiates general moral guidelines. Harmonization of the requirements of general morality and professional morality of civil servants is possible through the forms and methods of independent public control over the activities of individual specialists and the professional group as a whole. Defining and clearly formulating the mission of the civil service is the basis for building the entire system of professional ethics of civil servants and a factor in ensuring moral relations between government and citizens. The principle of serving the people is the semantic core around which the system of professional value orientations of civil servants should be built. The civil service sets standards of behavior in communication with citizens, representatives of various organizations and associations, behavior in communication with special respect, friendliness, politeness, restraint, impartiality, establishing business relations of officials with government officials, foreign delegations. Certainly, the main guidelines of the democratic civil service should be solidarity, justice, and respect for the human person.